2022
DOI: 10.1002/chem.202104385
|View full text |Cite
|
Sign up to set email alerts
|

Pd(II)‐Mediated C−H Activation for Cysteine Bioconjugation

Abstract: Selective bioconjugation remains a significant challenge for the synthetic chemist due to the stringent reaction conditions required by biomolecules coupled with their high degree of functionality. The current trailblazer of transition‐metal mediated bioconjugation chemistry involves the use of Pd(II) complexes prepared via an oxidative addition process. Herein, the preparation of Pd(II) complexes for cysteine bioconjugation via a facile C−H activation process is reported. These complexes show bioconjugation e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 40 publications
0
18
0
Order By: Relevance
“…The low abundance (ca. 1.7 %), unique reactivity of the sulfhydryl group and ease of incorporation by site‐directed mutagenesis allow cysteine to serve as an ideal residue for peptide/protein labeling [31–50] . In our previous studies on the modification of cysteine‐containing peptides and proteins, we found that electron‐deficient alkynones [36a] and isoxazoliniums [37c] were excellent reagents owing to their outstanding electrophilicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The low abundance (ca. 1.7 %), unique reactivity of the sulfhydryl group and ease of incorporation by site‐directed mutagenesis allow cysteine to serve as an ideal residue for peptide/protein labeling [31–50] . In our previous studies on the modification of cysteine‐containing peptides and proteins, we found that electron‐deficient alkynones [36a] and isoxazoliniums [37c] were excellent reagents owing to their outstanding electrophilicity.…”
Section: Resultsmentioning
confidence: 99%
“…1.7 %), unique reactivity of the sulfhydryl group and ease of incorporation by site-directed mutagenesis allow cysteine to serve as an ideal residue for peptide/protein labeling. [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] In our previous studies on the modification of cysteine-containing peptides and proteins, we found that electron-deficient alkynones [36a] and isoxazoliniums [37c] were excellent reagents owing to their outstanding electrophilicity. Along with our ongoing interest in the development of selective bioconjugation reactions, [36, 37, 51, we envisioned that the isoindolium-based allene 1, which exhibited excellent electrophilicity towards the sulfhydryl group, would be a useful handle for chemoselective modification of cysteine-containing peptides.…”
Section: Methodsmentioning
confidence: 99%
“…This strategy could allow for conjugation of polymers to proteins with limited stability at room temperature or which are only stable or soluble at non-neutral pH for the exploration of new biologics for therapeutic applications. Overall, this work represents an expansion of the growing organometallic reagent toolkit available for bioconjugation chemistry. ,, …”
Section: Discussionmentioning
confidence: 99%
“…Frost and coworkers have shown that Pd complexes for Cys arylation can be generated in situ from widely available Pd precursors, a method they have used for arylation of the free Cys34 of BSA, with 92–99% conversion. 119…”
Section: Cysteine (Cys)mentioning
confidence: 99%
“…Frost and coworkers have shown that Pd complexes for Cys arylation can be generated in situ from widely available Pd precursors, a method they have used for arylation of the free Cys34 of BSA, with 92-99% conversion. 119 The Pd-catalyzed Tsuji-Trost allylation reaction 120,121 has been used to introduce prenyl units on ubiquitin-like protein 3 (UBL3) and heat shock protein 27 (Hsp27) with a Pd/ BIPHEPHOS catalyst system. 122 Visible-light induced thiol-ene reactions.…”
Section: Biomaterials Sciencementioning
confidence: 99%